Development novice teachers' higher-order thinking skills through online problem-based learning platform: A mixed methods experimental research - Fongkanta, Pongwat; Buakanok, Fisik Sean (Jurnal Cakrawala Pendidikan, 2024)
One key competency in teaching profession is the ability to think at a higher level. Therefore, it is important to understand how to develop and refine effective training approaches for novice teachers. This study examined the novice teachers' higher-order thinking skills development through online problem-based learning platform and analyzed the level of novice teachers' higher-order thinking skills. The research involved 57 novice teachers participating in the research for learning development courses. The mixed method experimental design was employed in this study. Data were collected by using multiple choice tests and self-report reflective thinking forms. Descriptive statistics were used to analyze novice teachers' HOTS. The t-test was conducted to evaluate mean differences among the novice teachers' HOTS. Content analysis was used to code and categorize themes and pattern of HOTS perception. Results revealed that novice teachers have shown improvement in higher-order thinking skills include the problem solving, critical thinking, creative thinking sub-skills through online problem-based learning approach. Their proficiency in HOTS significantly increased, t(57) = 17.72, p < .001, with a high portion achieving advanced levels. Furthermore, they gained the positive perspective in employing online PBL for HOTS development.